TTF1-positive SMARCA4/BRG1 deficient lung adenocarcinoma - Anurag Mehta; Himanshi Diwan; Divya Bansal; Manoj Gupta (Korean Society of Pathologists & the Korean Society for Cytopathology, 2022)
SMARCA4/BRG1-deficient lung adenocarcinoma (SD-LUAD) is being recognized as a distinct subtype based on subtle differences in its clinical, morphological, and immunophenotypic attributes compared to other non-small cell lung carcinomas. We present here a case of SD-LUAD with curious thyroid transcription factor 1 (TTF1) expression in a morphologically heterogenous lung adenocarcinoma. The better differentiated area showed preservation of TTF1 expression, and a poorly differentiated tumor had loss of TTF1 expression with universal BRG1 loss.